Motivational Aspects of Teacher Collaboration - Kolleck, Nina (Frontiers in Education, 2019)
The mutual dependency of teacher collaboration and motivation has emerged as a promising research field. This article now sets out to systematically review peer-reviewed articles on the interconnection of these concepts. It looks at main findings, identifies ambiguities and contradictions in the constructs and highlights their contested nature. It is shown that many studies use different theoretical approaches and conceptual operationalizations. This leads to inconsistent empirical findings. In addition, teacher collaboration is often perceived as a threat to teacher autonomy. This is surprising considering that both teacher collaboration and teacher autonomy positively affect teacher motivation according to many empirical findings.